Obesity and sleep apnea as a significant comorbidities in COVID-19 — A case report. Issue 3 (May 2021) - Nikolic, Maja; Simovic, Stefan; Novkovic, Ljiljana; Jokovic, Vuk; Djokovic, Danijela; Muric, Nemanja; Bazic Sretenovic, Danijela; Jovanovic, Jovan; Pantic, Katarina; Cekerevac, Ivan
Abstract: In our paper we aimed to increase the awareness among physicians, concerning coronavirus disease 2019 (COVID-19) severity, especially in patients with specific underlying comorbidities. Obesity is the second most common condition in hospitalized COVID-19 patients. Furthermore it has a major role in the development of obstructive sleep apnoea (OSA), which is highly involved in a severe COVID-19 development and its serious outcomes. Even though obese OSA patients had an increased pulmonary embolism (PE) risk, there is no enough evidence to support the interaction between obesity and OSA regarding PE development in the setting of COVID-19. Our patient is a 45-year-old obese male with COVID-19, who was admitted to the intensive care unit (ICU) with acute respiratory failure requiring high-flow nasal oxygenation. Clinical, laboratory and diagnostic findings pointed on severe COVID-19 form, complicated with PE. After recovery, the diagnosis of OSA was established. With this case, we wanted to alert the physicians on comorbidities, such as obesity and OSA, while those conditions, to some extent, may contribute to worse COVID-19 clinical presentation.